Opportunities for international portfolio diversification in the Balkans’ markets - Dimitrios Dimitriou; Dimitris Kenourgios (International Journal of Economics and Research, 2012)
This paper examines long and short-run relationships among three emerging Balkan stock markets (Romania, Bulgaria and Croatia), two developed European stock markets (Germany and Greece) and United States (U.S.), during the period 2000 - 2005. We apply Johansen's (1988) cointegration methodology to test the long-run relationships between these markets and Granger's (1969) causality methodology in order to capture short-run cointegration. Our findings are mixed. We provide evidence on long-run relationships between the Bulgarian and Croatian stock markets and the developed markets. On the other hand, there is no any cointegration among the developed markets and the Romanian market. Moreover, there is no cointegrating relationship among the three regional emerging markets, while short-run relationships exist only among the region. These results have crucial implications for investors regarding the benefits of international portfolio diversification.